2007
DOI: 10.1143/jjap.46.3850
|View full text |Cite
|
Sign up to set email alerts
|

New Coaxial Interference Method for Consumer Holographic Memory

Abstract: We have developed a new coaxial interference method for the next-generation storage system. A signal beam and a reference beam are coaxially arranged and focused into a holographic medium using a bifocal lens. We can easily downsize the system because the optics is very simple. The reference beam is focused on the mirror surface of the medium, and the signal beam is defocused on this surface. A semicircular reference pattern is used to select normal playback or phase conjugate playback in a reproducing process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…( 13), the phase term is eliminated by using the sin and cos components in Eqs. (11) and (12). Because there is no phase term in Eq.…”
Section: X Y P I X Y P I X Y P B a X Y P A X Y Pmentioning
confidence: 99%
See 1 more Smart Citation
“…( 13), the phase term is eliminated by using the sin and cos components in Eqs. (11) and (12). Because there is no phase term in Eq.…”
Section: X Y P I X Y P I X Y P B a X Y P A X Y Pmentioning
confidence: 99%
“…Thanks to its transfer rate, recording density, reliability, low energy consumption, and longevity, holographic data storage (HDS) is a promising candidate to meet the demand. [1][2][3] Schemes such as angular multiplexing [4][5][6][7][8][9] and shift multiplexing [10][11][12][13] have been proposed for HDS. In HDS, two-dimensional data is recorded to a recording medium 14) as a three-dimensional hologram.…”
Section: Introductionmentioning
confidence: 99%
“…Needs of high density optical storage have been increasing since high capacity multimedia contents, such as 3D video contents and social media services become popular. Various optical storage technologies have been developed for high density storage including holographic data storage, [1][2][3] nearfield optical storage, [4][5][6] super resolution optical storage, [7][8][9] and two photon absorption storage 10,11) for next generation high density optical recording technologies. Recently, several studies on multi-layer Blu-ray disc (BD) system reported that the media consisting of three or four layers achieved over 100 Gbyte.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Recently, as a new dimension in the HDSS, a collinear holographic memory (CHM) has been developed to enhance the compatibility with a conventional optical disc drive. [6][7][8] Then, as a unique feature of the CHM, recording with collinear shift multiplexing and a reading process are executed through disc rotation, which makes it possible to achieve high data density and high data transfer rate simultaneously while maintaining technique compatibility. Thus far, Tanaka et al 9) have reported a coaxial holographic recording system with a storage density of 450 Gbyte/disc, which is nearly twenty times larger than that of a BD restricted by a two-dimensional diffraction limit.…”
Section: Introductionmentioning
confidence: 99%